Finding Margarethe Lutz. Issue 3 (1st September 2016) - Slavin, Jonathan H.; Rahmani, Miki
Abstract : The editors of this series of papers review their efforts to ascertain the identity of Margarethe Lutz and the provenance of the accounts she provided of her consultation with Sigmund Freud. There is considerable evidence that she conveyed fundamentally the same account, with emphasis on certain critical features of her experience, in many interviews and writings, privately and publicly. The editors briefly highlight the main points provided in each of the seven papers discussing this remarkable consultation and acknowledge the considerable assistance they have received from many individuals in investigating, verifying, and bringing these important papers to publication.